Regulation of Autophagy by Kinases - Sridharan, Savitha (Molecular Diversity Preservation International (MDPI), 2011)
Autophagy is a process of self-degradation that maintains cellular viability during periods of metabolic stress. Although autophagy is considered a survival mechanism when faced with cellular stress, extensive autophagy can also lead to cell death. Aberrations in autophagy are associated with several diseases, including cancer. Therapeutic exploitation of this process requires a clear understanding of its regulation. Although the core molecular components involved in the execution of autophagy are well studied there is limited information on how cellular signaling pathways, particularly kinases, regulate this complex process. Protein kinases are integral to the autophagy process. Atg1, the first autophagy-related protein identified, is a serine/threonine kinase and it is regulated by another serine/threonine kinase mTOR. Emerging studies suggest the participation of many different kinases in regulating various components/steps of this catabolic process. This review focuses on the regulation of autophagy by several kinases with particular emphasis on serine/threonine protein kinases such as mTOR, AMP-activated protein kinase, Akt, mitogen-activated protein kinase (ERK, p38 and JNK) and protein kinase C that are often deregulated in cancer and are important therapeutic targets.